1996
DOI: 10.1159/000244359
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Cerebral Hemodynamics and Oxygenation during Hypothermic Cardiopulmonary Bypass in Neonates and Infants

Abstract: Delay in development after open-heart surgery in infants has frequently been reported. Inadequate brain perfusion and oxygenation during deep hypothermic cardiopulmonary bypass (CPB) may play an important role. We investigated the effect of CPB on cerebral perfusion and oxygenation in 12 neonates and infants (age 0–11 months) undergoing open-heart surgery. Changes in cerebral blood volume (ΔCBV; in ml/100 g brain tissue) and oxidation level of the intracerebral mitochondrial enzyme cytochrome aa3 (Δ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 28 publications
1
10
0
1
Order By: Relevance
“…HT can significantly delay post-hypoxic electrographic changes in neonates [23] and decreased both cerebral oxygen metabolic rate and CBF in piglets [24] while increasing ScO 2 . van Bel et al also reported that CBV as measured by NIRS was reduced during HT in infants undergoing heart surgery [25]. We speculate that HT reduces hyperemia and edema, thereby decreasing CBV and improving outcome.…”
Section: Discussionsupporting
confidence: 55%
“…HT can significantly delay post-hypoxic electrographic changes in neonates [23] and decreased both cerebral oxygen metabolic rate and CBF in piglets [24] while increasing ScO 2 . van Bel et al also reported that CBV as measured by NIRS was reduced during HT in infants undergoing heart surgery [25]. We speculate that HT reduces hyperemia and edema, thereby decreasing CBV and improving outcome.…”
Section: Discussionsupporting
confidence: 55%
“…In a previous study, van Bel et al, 42 found CBV lowered during cooling and increased during rewarming in 12 neonates and infants (age 0 to 11 months) undergoing open-heart surgery using commercial continuous wave near infrared spectroscopy. 42 However, none of these neonates had documented brain injury, the degree of hypothermia was inconsistent among the patient population and there was no detail on the duration of cooling. An increase in CBV during rewarming was also noted using commercial continuous wave near infrared spectroscopy in seven out of eight neonates.…”
Section: Indices Of Cerebral Oxygen Metabolism and Cerebral Blood Flowmentioning
confidence: 92%
“…NIRS can also give estimates for the regional cerebral hemoglobin concentration (HbT), which is correlated with the regional cerebral blood volume [5]. Detection of cerebral hypoxemia in neonates [5] and cerebral monitoring during cardiopulmonary bypass [6] are among the possible clinical applications of NIRS. There are still problems in quantification, which prevent clinical applications of NIRS so far.…”
Section: Introductionmentioning
confidence: 99%